2020
DOI: 10.1111/evo.14048
|View full text |Cite
|
Sign up to set email alerts
|

Female prereproductive coloration reduces mating harassment in damselflies

Abstract: Conspicuous female coloration can evolve through male mate choice or via female-female competition thereby increasing female mating success. However, when mating is not beneficial, such as in pre-reproductive females, selection should favor cryptic rather than conspicuous coloration to avoid male detection and the associated harassment. Nevertheless, conspicuous female coloration occurs in many prereproductive animals, and its evolution remains an enigma. Here, I studied conspicuous female coloration in Agrioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 91 publications
(189 reference statements)
1
29
0
Order By: Relevance
“…In previous studies, female morphs of some species have been shown to differ in clutch size (Bots et al 2009(Bots et al , 2010bBouton et al 2011;Sánchez-Guillén et al 2017;Khan 2020) and egg size (Takahashi and Watanabe 2010b;Takahashi and Kawata 2013), but in other species there was no difference (Iserbyt et al 2013). In our study, we found a similar growth of larvae born from andromorph and gynomorph B-females.…”
Section: Larval Growthmentioning
confidence: 88%
“…In previous studies, female morphs of some species have been shown to differ in clutch size (Bots et al 2009(Bots et al , 2010bBouton et al 2011;Sánchez-Guillén et al 2017;Khan 2020) and egg size (Takahashi and Watanabe 2010b;Takahashi and Kawata 2013), but in other species there was no difference (Iserbyt et al 2013). In our study, we found a similar growth of larvae born from andromorph and gynomorph B-females.…”
Section: Larval Growthmentioning
confidence: 88%
“…These species are widely distributed in South Asia, South East Asia, and Australia [50][51]. They are commonly found in grasslands associated with ponds, lakes, marshes and in paddy fields, and cohabit with Ceriagrion coromandelianum, A. kalinga A. lacteola, and Orhterum sabina [49]. The males of A. femina are differentiated from other sympatric species by the size and shape of anal appendages (Epiproct larger than cerci) [50;Fig 1c].…”
Section: Study Systemsmentioning
confidence: 99%
“…Agriocnemis femina is a common damselfly in the northeastern region of Bangladesh [53,54], while A. pygmaea is commonly found in central and southwestern region of Bangladesh [49,55].…”
Section: Study Sitesmentioning
confidence: 99%
See 2 more Smart Citations